Developing morphological awareness across languages: translanguaging pedagogies in third language acquisition. Issue 1 (2nd January 2020) - Leonet, Oihana; Cenoz, Jasone; Gorter, Durk
ABSTRACT: This article focuses on the development of morphological awareness in English as a third language. It analyses how the activation of previous linguistic knowledge can influence morphological awareness. Participants were 104 primary school students who were learning English as a third language and were already fluent in two other languages, Basque and Spanish. Participants in the experimental group took part in a pedagogical intervention aiming at the development of morphological awareness by using translanguaging pedagogies. The aim of the intervention was to enable participants to use their linguistic repertoire across languages and benefit from their multilingual resources. Results indicate that participants in the experimental group obtained higher scores in morphological awareness than the control group from the same school. In addition, participants in the experimental group perceived that the use of translanguaging strategies was useful for their learning and also enjoyable as a teaching approach.